The Effect of Job Autonomy on Employee Innovative Behavior: The Role of Job Satisfaction as Intervening Variable - Nursiha Ramadani Nasution; Zulkifli Musannip Efendi Siregar; Pristiyono Pristiyono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Employee job satisfaction in covid-19 conditions and situations that need to be considered are those employees who work in Micro, Small, and Medium Enterprises (MSMEs) units. Interestingly, peeling employee job satisfaction in scientific studies is expected to provide various inputs to business managers or business owners who are controlled through work autonomy and innovative behavior in organizations. This research was conducted on the community in the Rantaurapat area around. The questionnaires collected were 100 questionnaires, the respondents in this study were 100 respondents. This research is research using quantitative methods, the researcher in this case distributes questionnaires to get data from respondents using Google Form, and then the data is analyzed using the help of SPSS 23 and AMOS version 23. Based on the results of research and discussion that have been trusted in the previous section, it can be concluded that work autonomy can increase job satisfaction in employees and be able to increase employee innovation behavior. The firm that can provide opportunities for their employees to develop and innovate without feeling pressured at work will provide satisfaction to these employees in working and advancing the company. The results of this study also indicate that job satisfaction did not mediate the effect of job satisfaction on innovation behavior, because the direct effect of job autonomy on innovative behavior was greater than indirect effect via job satisfaction.